Screening of α-glucosidase inhibitors in large-leaf yellow tea by offline bioassay coupled with liquid chromatography tandem mass spectrometry - You Wu; Zisheng Han; Mingchun Wen; Chi-Tang Ho; Zongde Jiang; Yijun Wang; Na Xu; Zhongwen Xie; Jinsong Zhang; Liang Zhang; Xiaochun Wan (Food Science and Human Wellness)
Larger-leaf yellow tea (LYT) is a characteristic type of Chinese tea produced in Huoshan County, Anhui Province, which is made by mature leaves with stems. According to recent report, LYT showed competitive effects in anti-hyperglycemia in comparison to other teas such as green or black tea. However, the bioactive compounds of LYT are still undiscovered so far. For this purpose, 5 fractions of LYT were prepared by sequential extraction. The in vitro bioassay results indicated that the ethyl acetate fraction of LYT had the strongest inhibitory effects on α-glucosidase and α-amylase. Fluorescence-quenching analysis and protein-binding test revealed that the compounds of ethyl acetate fraction could inhibit α-glucosidase and α-amylase activities through binding to enzymes or other mechanisms. All chromatographic peaks of high-performance liquid chromatography (HPLC) of ethyl acetate fraction were separated and collected. The purified compounds were identified by liquid chromatography-mass spectrometry (LC-MS), and subsequently screened by calculating their inhibition ratio on α-glucosidase at the real concentration in LYT infusion. The results showed that (–)-epigallocatechin gallate, (–)-gallocatechin gallate, caffeine, N-ethyl-2-pyrrolidone-substituted flavan-3-ols were effective inhibitors for α-glucosidase.